Composite and method for producing the composite

JP7643152B2Active Publication Date: 2025-03-11TOYOTA BOSHOKU KK
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021066978
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-04-12
Publication Date
2025-03-11
Estimated Expiration
2041-04-12

AI Technical Summary

Benefits of technology

【0007】 本開示の複合体は、従来のポリアミド化合物よりも優れた特性を有する。 本開示の製造方法によれば、従来のポリアミド化合物よりも優れた特性を有する複合体を製造できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007643152000021
    Figure 0007643152000021
  • Figure 0007643152000022
    Figure 0007643152000022
  • Figure 0007643152000023
    Figure 0007643152000023
Patent Text Reader

Abstract

To provide a novel composite.SOLUTION: The composite contains a polyamide compound and talc. The polyamide compound comprises a dicarboxylic acid unit represented by the specified general formula (1), a dicarboxylic acid unit represented by the specified general formula (2), and a particular diamine unit represented by the specified general formula (3). In the general formula (1), x is an integer from 6 to 12; and y is an integer from 8 to 18. In the general formula (2), z is an integer from 2 to 18.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to composites and methods for making the composites. [Background technology]

[0002] From the viewpoints of preventing global warming and reducing resource risks, biopolymers such as polyamide compounds made from plant-derived compounds as starting materials have been attracting attention as alternatives to petroleum-based polymers (see, for example, Non-Patent Documents 1-2 and Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2019-137788 A [Non-patent literature]

[0004] [Non-Patent Document 1] C. -H. Lee, H. Takagi, H. Okamoto, M. Kato, A. Usuki. J. Polym. Sci. Part A: Polym. Chem. 47, 6025 (2009). [Non-Patent Document 2] C. -H. Lee, H. Takagi, H. Okamoto, M. Kato. J. Appl. Polym. Sci. 127, 530 (2013). Summary of the Invention [Problem to be solved by the invention]

[0005] However, conventional biopolymers do not necessarily have sufficient properties for some applications, and there is a demand for improved properties. The present disclosure is intended to solve the above problems and can be realized in the following forms. [Means for solving the problem]

[0006] 1. A polyamide compound containing a dicarboxylic acid unit represented by the following general formula (1), a dicarboxylic acid unit represented by the following general formula (2), and a diamine unit represented by the following general formula (3), Talc and A complex comprising: [ka] (wherein x is an integer from 6 to 12, and y is an integer from 8 to 18.) [ka] (z is an integer from 2 to 18.) [ka] [ka] Effect of the Invention

[0007] The composites of the present disclosure have superior properties to conventional polyamide compounds. According to the manufacturing method of the present disclosure, a composite having superior properties to those of conventional polyamide compounds can be manufactured. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a graph showing tensile strength. [Diagram 2] FIG. 2 is a graph showing the tensile modulus. [Diagram 3] FIG. 3 is a graph showing the flexural modulus. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Here, another example of the present disclosure is given. A complex, wherein the molar ratio of the dicarboxylic acid unit represented by general formula (1):the dicarboxylic acid unit represented by general formula (2) is 95:5 to 5:95. The complex, wherein the talc content is 1% by mass or more and 40% by mass or less. A method for producing a composite, comprising kneading the polyamide compound and the talc in a twin-screw kneading extruder.

[0010] Hereinafter, the embodiments of the present disclosure will be described in detail. In this specification, when a numerical range is described using "to", the range includes the lower limit and the upper limit unless otherwise specified. For example, the description "10 to 20" includes both the lower limit "10" and the upper limit "20". In other words, "10 to 20" has the same meaning as "10 or more and 20 or less".

[0011] The present disclosure will be described in detail below. 1. Complex The composite contains talc and a polyamide compound containing a dicarboxylic acid unit represented by the following general formula (1), a dicarboxylic acid unit represented by the following general formula (2), and a diamine unit represented by the following general formula (3). [ka] (wherein x is an integer from 6 to 12, and y is an integer from 8 to 18.) [ka] (z is an integer from 2 to 18.) [ka] [ka]

[0012] 1.1 Polyamide compounds The polyamide compound of the present disclosure may further contain structural units other than those described above, as long as the effects of the present disclosure are not impaired.

[0013] In the polyamide compound of the present disclosure, the content of the dicarboxylic acid unit is not particularly limited and is usually 5 to 50 mol %, preferably 20 to 50 mol %, and more preferably 30 to 50 mol %. In the polyamide compound of the present disclosure, the content of the diamine unit is not particularly limited and is usually 5 to 50 mol %, preferably 20 to 50 mol %, and more preferably 30 to 50 mol %. From the viewpoint of the polymerization reaction, the content ratio of the dicarboxylic acid unit and the diamine unit is preferably approximately the same, and the content of the dicarboxylic acid unit is more preferably within ±1 mol % of the content of the diamine unit.

[0014] 1.1.1 Dicarboxylic acid unit As described above, the polyamide compound of the present disclosure contains a dicarboxylic acid unit represented by the following general formula (1) and a dicarboxylic acid unit represented by the following general formula (2). [ka] (x is an integer from 6 to 12, and y is an integer from 8 to 18. x is preferably an integer from 8 to 10, and y is preferably an integer from 8 to 14. [ka] (z represents an integer from 2 to 18. z is preferably an integer of 2 to 6.

[0015] The dicarboxylic acid unit represented by the general formula (1) is derived from plants and contributes to preventing global warming and reducing resource risks.

[0016] When the total amount of dicarboxylic acid units in the polyamide compound of the present disclosure is taken as 100 mol%, the total amount of dicarboxylic acid units represented by the above general formulas (1) and (2) is not particularly limited. The total amount of dicarboxylic acid units represented by the general formulas (1) and (2) is preferably 30 to 100 mol%, more preferably 50 to 100 mol%, and particularly preferably 70 to 100 mol%. When the content of the dicarboxylic acid units represented by the general formulas (1) and (2) is within this range, a composite having a high bending modulus can be obtained. Furthermore, when the content is within this range, a composite having a high glass transition temperature (Tg) can be obtained.

[0017] In the polyamide compound, the molar ratio of the dicarboxylic acid unit represented by the general formula (1) to the dicarboxylic acid unit represented by the general formula (2) is not particularly limited. The molar ratio of the dicarboxylic acid units represented by general formula (1):the dicarboxylic acid units represented by general formula (2) is preferably 95:5 to 5:95, more preferably 90:10 to 10:90, and further preferably 80:20 to 20:80.

[0018] Compounds capable of constituting dicarboxylic acid units other than the dicarboxylic acid units represented by the general formulae (1) and (2) are not particularly limited. For example, specific examples of dicarboxylic acid compounds include straight-chain aliphatic dicarboxylic acids having 2 to 25 carbon atoms, such as oxalic acid, malonic acid, fumaric acid, and maleic acid, or aliphatic dicarboxylic acids such as dimerized aliphatic dicarboxylic acids having 14 to 48 carbon atoms (dimer acids) obtained by dimerizing unsaturated fatty acids obtained by fractional distillation of triglycerides and hydrogenated products thereof (hydrogenated dimer acids), alicyclic dicarboxylic acids such as 1,4-cyclohexanedicarboxylic acid, and aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 1,3-benzenediacetic acid, and 1,4-benzenediacetic acid. Derivatives of these dicarboxylic acid compounds may also be used. Examples of derivatives include carboxylic acid halides. These may be used alone or in combination of two or more. When the total amount of dicarboxylic acid units in the polyamide compound of the present disclosure is 100 mol%, the content of dicarboxylic acid units other than the dicarboxylic acid represented by the above general formula (1) and (2) is not particularly limited. The content of dicarboxylic acid units other than the dicarboxylic acid represented by the general formula (1) and (2) is preferably less than 50 mol%, more preferably less than 20 mol%, and particularly preferably less than 10 mol%. When the content of dicarboxylic acid units other than the dicarboxylic acid units represented by the general formula (1) and (2) is within this range, the tensile strength, tensile modulus, flexural modulus, etc. are improved.

[0019] 1.1.2 Diamine units The diamine unit in the polyamide compound of the present disclosure includes at least a diamine unit represented by general formula (3). [ka] [ka]

[0020] When the total amount of diamine units in the polyamide compound of the present disclosure is taken as 100 mol%, the content of the diamine units represented by the above general formula (3) is not particularly limited. The diamine units represented by the general formula (3) are preferably contained at 5 to 100 mol%, more preferably at 50 to 100 mol%, and particularly preferably at 80 to 100 mol%. When the content of the diamine acid units represented by the general formula (3) is within this range, the tensile strength, tensile modulus, bending elasticity, etc. are excellent.

[0021] Repeating units which may be contained in the polyamide compound include the following combinations of dicarboxylic acid units and diamine units. [A] A combination of a dicarboxylic acid unit represented by general formula (1) and a diamine unit represented by general formula (3). [B] A combination of a dicarboxylic acid unit represented by general formula (2) and a diamine unit represented by general formula (3). Different types of repeating units may be present randomly in the polyamide compound. Furthermore, the same kind of repeating units may be present in the polyamide compound in the form of blocks.

[0022] Compounds capable of constituting diamine units other than the diamine unit represented by formula (3) are not particularly limited. For example, examples of diamines other than the diamine unit represented by formula (3) include known aliphatic diamines, alicyclic diamines, aromatic diamines, and diaminoorganosiloxanes.

[0023] Examples of aliphatic diamines that can form diamine units other than the diamine unit represented by formula (3) include 1,1-metaxylylenediamine, 1,3-propanediamine, and pentamethylenediamine. Examples of the alicyclic diamine include 4,4'-methylenebis(cyclohexylamine) and 1,3-bis(aminomethyl)cyclohexane. Examples of aromatic diamines include o-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylmethane, 1,5-diaminonaphthalene, 2,2'-dimethyl-4,4'-diaminobiphenyl, 4,4'-diamino-2,2'-bis(trifluoromethyl)biphenyl, 2,7-diaminofluorene, 4,4'-diamino-2,2'-dimethylbiphenyl, 9,9-bis(4-aminophenyl)fluorene, 2,2-bis[4-(4-aminophenoxy)phenyl]hexafluoropropane, 2,2-bis(4-aminophenyl)heptane, and the like. xafluoropropane, 4,4'-(p-phenylenediisopropylidene)bisaniline, 4,4'-(m-phenylenediisopropylidene)bisaniline, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, 2,6-diaminopyridine, 3,4-diaminopyridine, 2,4-diaminopyrimidine, 3,6-diaminoacridine, 3,6-diaminocarbazole, N-methyl-3,6-diaminocarbazole, N-ethyl-3,6-diaminocarbazole, N-phenyl-3,6-diaminocarbazole azole, N,N'-bis(4-aminophenyl)-benzidine, N,N'-bis(4-aminophenyl)-N,N'-dimethylbenzidine, 1,4-bis(4-aminophenyl)-piperazine, 3,5-diaminobenzoic acid, dodecanoxy-2,4-diaminobenzene, tetradecanoxy-2,4-diaminobenzene, pentadecanoxy-2,4-diaminobenzene, hexadecanoxy-2,4-diaminobenzene, octadecanoxy-2,4-diaminobenzene, dodecanoxy-2,5-diaminobenzene, tetradecanoxy-2,5-diaminobenzidine benzene, pentadecanoxy-2,5-diaminobenzene, hexadecanoxy-2,5-diaminobenzene, octadecanoxy-2,5-diaminobenzene, cholestanyloxy-3,5-diaminobenzene, cholestanyloxy-3,5-diaminobenzene, cholestanyloxy-2,4-diaminobenzene, cholestanyloxy-2,4-diaminobenzene, cholestanyl 3,5-diaminobenzoate, cholestanyl 3,5-diaminobenzoate, lanostannyl 3,5-diaminobenzoate, 3,6-bis(4-aminobenzoyloxy)cholestane, 3,6-bis(4-aminophenoxy)cholestane, 4-(4'-trifluoromethoxybenzoyloxy)cyclohexyl-3,5-diaminobenzoate, 4-(4'-trifluoromethylbenzoyloxy)cyclohexyl-3,5-diaminobenzoate, 1,1-bis(4-((aminophenyl)methyl)phenyl)-4-butylcyclohexane, 1,1-bis(4-((aminophenyl)methyl)phenyl)-4-heptylcyclohexane, 1,1-bis(4-((aminophenoxy)methyl)phenyl)-4-heptylcyclohexane Examples of the aryl group include cyclohexane, 1,1-bis(4-((aminophenyl)methyl)phenyl)-4-(4-heptylcyclohexyl)cyclohexane, 2,4-diamino-N,N-diallylaniline, 4-aminobenzylamine, 3-aminobenzylamine, 1-(2,4-diaminophenyl)piperazine-4-carboxylic acid, 4-(morpholin-4-yl)benzene-1,3-diamine, 1,3-bis(N-(4-aminophenyl)piperidinyl)propane, and α-amino-ω-aminophenylalkylene. These may be used alone or in combination of two or more.

[0024] When the total amount of diamine units in the polyamide compound of the present disclosure is 100 mol%, the content of diamine units other than the diamine represented by the above general formula (3) is not particularly limited. The content of diamine units other than the diamine represented by the general formula (3) is preferably less than 50 mol%, more preferably less than 30 mol%, and particularly preferably less than 10 mol%. When the content of diamine units other than the diamine represented by the general formula (3) is within this range, the tensile strength, tensile modulus, bending elasticity, etc. are improved.

[0025] 1.1.3 Degree of polymerization of polyamide compounds The degree of polymerization of the polyamide compound of the present disclosure is not particularly limited. The viscosity number measured as follows is preferably in the range of 4.0 to 10.0, particularly preferably in the range of 5.0 to 8.0. The viscosity number is measured as follows. Test method: JIS K6933 compliant Test conditions: Measurement solvent: 96% sulfuric acid Viscometer: Ubbelohde viscometer Solution concentration: 0.005g / mL Measurement temperature: 25℃ Calculation formula: Viscosity number (mL / g)=(t / t0-1)×1 / C t0: Flow time of the measurement solvent (s) t: Flow time of sample solution (s) C: Solution concentration (g / mL)

[0026] 1.1.4 Manufacturing method of polyamide compounds The method for producing the polyamide compound of the present disclosure is not particularly limited. The polyamide compound of the present disclosure can be produced, for example, by reacting a dicarboxylic acid compound with a diamine compound.

[0027] As the dicarboxylic acid compound, in addition to dicarboxylic acids, carboxylic acid derivatives in which the hydroxyl group of the carboxyl group of a dicarboxylic acid is replaced with another heteroatom (an atom other than carbon, hydrogen, or metal) can also be used. Examples of the carboxylic acid derivatives include acyl halides (acid halides) in which the hydroxyl group is replaced with a halogen.

[0028] The polyamide compound of the present disclosure can be produced by polycondensing a diamine component capable of forming a diamine unit and a dicarboxylic acid component capable of forming a dicarboxylic acid unit. The degree of polymerization can be controlled by adjusting the polycondensation conditions, etc. The method for producing the polyamide compound is not particularly limited. For example, the method for producing the polyamide compound may be preferably, for example, (1) a method using an acid or base catalyst, (2) a method using a carboxylic acid, (3) a method using transesterification, or (4) a method using a condensing agent.

[0029] As a suitable production method, for example, a production method is adopted in which a dicarboxylic acid is activated to produce an acid chloride, and the acid chloride is reacted with a diamine to produce a polyamide compound. That is, a production method is preferably adopted in which an acid chloride capable of forming a dicarboxylic acid unit represented by the above general formula (1), an acid chloride capable of forming a dicarboxylic acid unit represented by the above general formula (2), and a diamine capable of forming a diamine unit represented by the above general formula (3) are reacted. In addition, if a dicarboxylic acid is activated to form an acid chloride and then reacted with a diamine, a polyamide compound can be produced efficiently.

[0030] In addition, a monoamine or a monocarboxylic acid may be added as a molecular weight regulator during polycondensation. In order to suppress the polycondensation reaction and achieve a desired degree of polymerization, the ratio (molar ratio) of the diamine component and the carboxylic acid component constituting the polyamide compound may be adjusted to be different from 1.

[0031] When polymerization is carried out by a dehydrohalogenation reaction between a carboxylic acid dihalide such as the above-mentioned acid chloride and a diamine, it is preferable to carry out the reaction at a relatively low temperature in order to control the reaction rate, since the reaction proceeds rapidly. For example, it is preferable to carry out the treatment at a temperature in the range of -10°C to 100°C. The reaction solvent is not particularly limited, and a wide variety of known solvents can be used. For example, examples of organic polar solvents as reaction solvents include dimethylacetamide, N-methylpyrrolidone, dimethylsulfone, dimethylformamide, N-methylcaprolactam, tetramethylurea, and N,N'-dimethyl-2-imidazolidinone. These may be used alone or as a mixed solvent of two or more. If necessary, hydrogen chloride or a metal halide salt, such as lithium chloride, calcium chloride, or potassium chloride, may be used in combination to improve solubility.

[0032] The concentration of the polyamide compound (polymer concentration) is not particularly limited, although it depends on the solubility of the produced polyamide compound in a solvent and the solution viscosity. The concentration of the polyamide compound is preferably 0.1 to 40 mass % from the viewpoint of productivity, for example. The concentration of the polyamide compound is determined by comprehensively considering the content and composition ratio of the polyamide compound composition, solubility, solution viscosity, handleability, and ease of degassing.

[0033] The method of adding the raw materials is not particularly limited. For example, a diamine is added to a reaction solvent, and after dissolving at a low temperature, a dicarboxylic acid halide such as an acid chloride, which is one of the raw materials, is added. In this case, it is preferable to carry out the reaction under an inert atmosphere (for example, under a nitrogen atmosphere or an argon gas atmosphere) in order to prevent deterioration of the diamine. The molar ratio of the diamine and the acid halide should basically be equimolar, but in order to control the degree of polymerization, the diamine or the acid component, which is one of the raw materials, may be added in excess, or a monofunctional organic compound, such as aniline, naphthylamine, acetic acid chloride, or benzoyl chloride, may be added in an appropriate amount.

[0034] In the case of the polyamide compound of the present disclosure, in order to improve the properties, a method of addition intended to block the polymer may be adopted in which a part of the diamine or acid chloride is reacted and then the remaining raw materials are added.

[0035] The polymerization reaction product (polyamide compound) thus obtained contains hydrogen halide as a by-product, and therefore requires neutralization. The neutralizing agent is not particularly limited as long as it is a commonly known basic compound. As the neutralizing agent, triethylamine, tripropylamine, benzyldimethylamine, lithium hydroxide, sodium hydroxide, potassium hydroxide, magnesium hydroxide, calcium hydroxide, magnesium oxide, calcium oxide, tetraethylammonium salt, etc. Although such a neutralizing agent may be added alone in the form of a powder, it is preferable to use a finely powdered neutralizing agent dispersed in an organic solvent as a slurry in terms of reactivity and operability.

[0036] The polyamide compound solution obtained by the above method can be separated in a poor solvent such as water, methanol, etc. The solution after the neutralization reaction can also be used as it is as a molding solution.

[0037] In addition, the industrial polycondensation method of the polyamide compound of the present disclosure is not particularly limited, and known methods are widely used. For example, the pressurized salt method, the normal pressure dropping method, the pressurized dropping method, the reactive extrusion method, etc. are included. In addition, the reaction temperature is as low as possible, so that the yellowing and gelation of the polyamide compound can be suppressed, and the polyamide compound with stable properties can be obtained.

[0038] The pressurized salt method is a method of melt polycondensation under pressure using nylon salt as a raw material. Specifically, after preparing an aqueous nylon salt solution containing a diamine component, a dicarboxylic acid component, and optionally other components, the aqueous solution is concentrated and then heated under pressure to polycondense while removing condensation water. While gradually returning the pressure inside the vessel to normal pressure, the temperature is raised to about the melting point of the polyamide compound +10°C and maintained, and then the pressure is gradually reduced to 0.02 MPaG while maintaining the temperature to continue polycondensation. When a certain stirring torque is reached, the inside of the vessel is pressurized to about 0.3 MPaG with nitrogen to recover the polyamide compound.

[0039] In the normal pressure dropping method, a diamine component is continuously dropped into a mixture of a dicarboxylic acid component and, if necessary, other components, which are heated and melted under normal pressure, and polycondensation is carried out while removing the condensed water. Note that the polycondensation reaction is carried out while increasing the temperature of the reaction system so that the reaction temperature does not fall below the melting point of the polyamide compound to be produced.

[0040] In the pressure dropping method, first, a dicarboxylic acid component and, if necessary, other components are charged into a polycondensation tank, and each component is stirred and melted and mixed to prepare a mixture. Next, the diamine component is continuously dropped into the mixture while pressurizing the inside of the tank to about 0.3 to 0.4 MPaG, and polycondensation is performed while removing condensation water. At this time, the polycondensation reaction is performed while raising the temperature of the reaction system so that the reaction temperature does not fall below the melting point of the polyamide compound to be produced. When the set molar ratio is reached, the dropping of the diamine component is terminated, and while gradually returning the inside of the tank to normal pressure, the temperature is raised to about the melting point + 10 ° C of the polyamide compound and maintained, and then the temperature is gradually reduced to 0.02 MPaG while maintaining the temperature, and polycondensation is continued. When a certain stirring torque is reached, the inside of the tank is pressurized to about 0.3 MPaG with nitrogen to recover the polyamide compound. The reactive extrusion method is a method for incorporating the compound into the polyamide backbone by a transamidation reaction.

[0041] 1.2 Talc The talc is not particularly limited. For example, talc is a plate-like particle of magnesium silicate having a layered structure, and its composition is, for example, Mg3Si4O 10 (OH)2 and other minerals. The content of talc in the composite is not particularly limited, but from the viewpoint of improving the tensile strength, tensile modulus, flexural modulus, etc. of the composite, the content of talc is preferably 1% by mass or more and 40% by mass or less, more preferably 2% by mass or more and 30% by mass or less, and even more preferably 5% by mass or more and 20% by mass or less, based on 100% by mass of the entire composite.

[0042] 1.2.1 Particle size (D50) The particle size (D50) (median size) of the talc is not particularly limited. From the viewpoint of improving the tensile strength, tensile modulus, flexural modulus, etc. of the composite, the particle size (D50) of the talc is preferably 0.1 μm or more and 50 μm or less, more preferably 0.5 μm or more and 25 μm or less, and even more preferably 2 μm or more and 8 μm or less. The particle size (D50) can be measured by a laser diffraction method.

[0043] 1.2.2 Apparent density The apparent density of the talc is not particularly limited. From the viewpoint of improving the tensile strength, tensile modulus, flexural modulus, etc. of the composite, the apparent density of the talc is preferably 0.05 g / mL or more and 0.7 g / mL or less, more preferably 0.08 g / mL or more and 0.6 g / mL or less, and even more preferably 0.1 g / mL or more and 0.5 g / mL or less. The apparent density can be measured according to JIS K5101.

[0044] 1.2.3 Specific surface area The specific surface area of ​​the talc is not particularly limited. From the viewpoint of improving the tensile strength, tensile modulus, flexural modulus, etc. of the composite, the specific surface area of ​​the talc is preferably 1.5 m 2 / g or more 100m 2 / g or less is preferable, and 3m 2 / g or more 20m 2 / g or less is more preferable, and 5m 2 / g or more 10m 2 The specific surface area can be measured by the BET method.

[0045] 1.2.4 Moisture The moisture content of the talc is not particularly limited. From the viewpoint of improving the tensile strength, tensile modulus, flexural modulus, etc. of the composite, the moisture content of the talc is preferably 0.1% or more and 0.5% or less, more preferably 0.1% or more and 0.3% or less. The moisture content can be measured in accordance with JIS K5101.

[0046] 1.2.5 Oil absorption The oil absorption of the talc is not particularly limited. From the viewpoint of improving the tensile strength, tensile modulus, flexural modulus, etc. of the composite, the oil absorption of the talc is preferably 20 ml / 100 g or more and 60 ml / 100 g or less, more preferably 20 ml / 100 g or more and 60 ml / 100 g or less. The oil absorption can be measured in accordance with JIS K5101.

[0047] 1.2.6 Chromaticity The whiteness of the talc is not particularly limited. The whiteness of the talc is preferably 90% or more and 100% or less, more preferably 95% or more and 100% or less, in order to suppress the influence of impurities on the tensile strength, tensile modulus, flexural modulus, etc. of the composite. The whiteness can be measured by the Hunter method.

[0048] 1.3 Properties of the Complex In the composite of the present disclosure, talc is well dispersed in the polyamide compound, and therefore the composite has high tensile strength, tensile modulus, and flexural elasticity. In general synthetic polymers, the dispersibility of talc is not so high. However, in the composite of the present disclosure, the dispersibility of talc is high. The reason for this is presumed to be as follows. In the polyamide compound used in the composite of the present disclosure, the amide bond has a high affinity with the hydroxyl group of talc, and further, the long alkyl chain (nC x H 2x+1 It is presumed that the high affinity of these metals with the Mg, Si, etc. in talc increases the dispersibility of talc. Furthermore, when x=9 and y=11 in the above general formula (1), the dicarboxylic acid unit represented by the above general formula (1) is derived from plants, and talc is a natural mineral, making the complex environmentally friendly. These characteristics are not available in composites made from conventional synthetic polymers.

[0049] 1.4 Additives Depending on the application and performance, additives such as lubricants, crystallization nucleating agents, whitening inhibitors, matting agents, heat stabilizers, weathering stabilizers, ultraviolet absorbers, plasticizers, flame retardants, antistatic agents, coloring inhibitors, antioxidants, impact modifiers, etc. These additives can be added as necessary to the extent that they do not impair the effects of the composite of the present disclosure.

[0050] 1.5 Uses of the composite The composites of the present disclosure can be used in a wide range of applications.

[0051] 2. Manufacturing method of the composite The method for producing the composite is not particularly limited. The composite can be suitably produced by kneading a polyamide compound and talc in a twin-screw kneading extruder. EXAMPLES

[0052] The present disclosure will be described in more detail below with reference to examples. In the following description, the polyamide compound may also be referred to as a "biopolymer." The composite may also be referred to as a "biopolymer composite material."

[0053] 1. Synthesis of polyamide compounds (PA 80 AC 20 BPE 100 Synthesis of Polyamide compounds (PA 80 AC 20 BPE 100 The synthesis of was carried out according to the following scheme, where Z=4.

[0054] [ka]

[0055] In detail, 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BPE) (41.1g, 100.0mmol) and THF (300mL) were placed in a separable flask (1000mL) under a nitrogen atmosphere, and the mixture was stirred at 0℃ for 10 minutes using a mechanical stirrer. After that, triethylamine (30.8mL, 220.0mmol) was added and stirred at 0℃ for 10 minutes. Then, acid chloride (1') (57.2g, 80.0mmol) and adipol chloride (3.7g, 20.0mmol) were dissolved in THF (100mL) and added dropwise, and the mixture was reacted at 0℃ for 4 hours. After the reaction was completed, the product was purified by reprecipitation using water and washed with water and methanol. The product was vacuum dried (80℃, 16 hours). White fibrous product, yield: 92.0g. FT-IR (ATR, cm -1):3290.0(NH,amide),2918.7,2854.1,1653.7(C=O,carbonyl),1601.6,1533.1,1497.5,1461.8,1409.7,1222.6,1174.4,1014.4,831.2,727.0,512.0. The polyamide compound was pelletized. The chemical formula of this polyamide compound is shown below.

[0056] [ka]

[0057] 2. Complex Preparation The polyamide compound (PA 80 AC 20 BPE 100 90 parts by mass of the cellulose acetate copolymer and 10 parts by mass of talc were mixed in a twin-screw mixer / extruder to obtain a composite material. The composite material was pelletized. When the composite was observed by scanning electron microscope (SEM), the morphology was confirmed that talc was uniformly dispersed in the polyamide compound.

[0058] 3. Mechanical property evaluation 3.1 Preparation of test specimens Test pieces were made from the pellets using an injection molding machine (small electric injection molding machine SE18DUZ, manufactured by Sumitomo Heavy Industries, Ltd.). The molding conditions were a resin temperature of 160-240°C and a mold temperature of 14-18°C. Test pieces were molded into JIS K7161 (t=2mm) multipurpose test piece 5A type (dumbbell-shaped) and 10mm wide x 80mm long x 4mm thick test pieces (strip-shaped). The dumbbell-shaped test pieces were used for tensile tests. The strip-shaped test pieces were processed into K7110 type 1 test pieces and used for Charpy impact tests and bending tests.

[0059] 3.2 Tensile test The tensile properties were evaluated by conducting a tensile test in accordance with JIS K 7161-2, and the yield stress (tensile strength), tensile breaking strain, and tensile modulus were evaluated. The width and thickness of the test piece were measured and used for the measurement. A universal material testing machine Model 5966 (manufactured by Instron) was used for the measurement. The measurement conditions were a tensile speed of 100 mm / min, a tensile load of 50 kN, and a measurement temperature of 23°C.

[0060] 3.3 Bending test The bending properties were evaluated by a bending test to evaluate the bending modulus and bending strength. The bending test was conducted in accordance with JIS K7171. The width and thickness of the test piece were measured. A universal material testing machine Model 5966 (manufactured by Instron) was used for the measurement. The measurement conditions were a test speed of 2 mm / min, a maximum load of 10 kN, and a measurement temperature of 23°C.

[0061] 3.4 Charpy impact test The impact properties were evaluated by performing a notched Charpy test to determine the Charpy impact value. The bending test was performed in accordance with JIS K7111-1. The width and thickness of the test pieces were measured. A Charpy impact tester, Toyo Seiki Seisakusho DG-UB, was used for the measurements.

[0062] 3.5 Test Results The test results are shown in Table 1 and Figures 1 to 3.

[0063] [Table 1]

[0064] The test results in Table 1 and Figures 1 to 3 show that the composite has significantly higher tensile strength, tensile modulus, and flexural modulus than the biopolymer alone.

[0065] 4. Physical property evaluation 4.1 Measurement method The glass transition temperature (Tg) was determined by differential scanning calorimetry (DSC). The 5% weight loss temperature (Td) was determined by simultaneous thermogravimetry and differential thermal analysis (TG / DTA). Tg was measured in accordance with JIS K7121. Td and thermal decomposition temperature were measured in accordance with JIS K7120. The measurements were performed using thermal analyzers EXSTAR DSC7020 manufactured by Hitachi High-Tech Science Corporation and TG8120 manufactured by Rigaku Corporation under the following measurement conditions. The DSC measurement was performed at a temperature range of −50 to 280° C., at a temperature rise rate of 10° C. / min, in a nitrogen gas flow (50 mL / min). The TG / DT measurements were performed at a measurement temperature of room temperature to 500° C., at a temperature rise rate of 10° C. / min, in a nitrogen gas flow (150 mL / min).

[0066] 4.2 Measurement results The measurement results are shown in Table 2.

[0067] [Table 2]

[0068] The measurement results in Table 2 confirm that the complex has higher thermal stability than the biopolymer alone.

[0069] 5. Effects of the embodiment The composites of the examples have excellent mechanical properties and also have excellent thermal stability.

[0070] The above examples are merely illustrative and should not be construed as limiting the present disclosure. Although the present disclosure has been described with examples of typical embodiments, the words used in describing and illustrating the present disclosure are understood to be descriptive and exemplary, rather than limiting. As detailed herein, changes may be made within the scope of the appended claims without departing from the scope or nature of the present disclosure in its form. Although specific structures, materials, and examples have been referred to in the detailed description of the present disclosure, it is not intended that the present disclosure be limited to the disclosures herein, but rather that the present disclosure extends to all functionally equivalent structures, methods, and uses within the scope of the appended claims.

[0071] The present disclosure is not limited to the above-described embodiments, and various modifications and variations are possible within the scope of the claims of the present disclosure. [Industrial Applicability]

[0072] The composite of the present disclosure can be used in a wide range of applications, including those for which conventional polyamide compounds have been used. For example, it can be used as any member of an automobile, a railroad vehicle, a ship, an airplane, etc. For example, it can be used as an interior material and an exterior material. Among these, examples of automotive products include interior materials for automobiles, instrument panels for automobiles, and exterior materials for automobiles. Specific examples include door substrates, package trays, pillar garnishes, switch bases, quarter panels, side panels, armrests, automobile door trims, seat structural materials, seat backboards, ceiling materials, console boxes, automobile dashboards, various instrument panels, deck trims, bumpers, spoilers, cowlings, etc. Furthermore, examples of the composite can include interior materials and exterior materials for buildings, furniture, etc. That is, examples of the composite can include door covering materials, door structural materials, and covering materials for various furniture (desks, chairs, shelves, chests, etc.). Other examples of the composite can include packaging bodies, containers (trays, etc.), protective members, partition members, etc.

Claims

1. A polyamide compound containing a dicarboxylic acid unit represented by the following general formula (1), a dicarboxylic acid unit represented by the following general formula (2), and a diamine unit represented by the following general formula (3), Talc and Including, It does not include a modified polyester elastomer obtained by reacting a monomer selected from unsaturated carboxylic acids and unsaturated carboxylic acid derivatives with a polyester elastomer, Does not contain styrene resins containing rubber polymers, Does not contain polyphenylene ether The composite does not contain a rubbery polymer. 【Chemistry 1】 (wherein x is an integer from 6 to 12, and y is an integer from 8 to 18.) 【Chemistry 2】 (z is an integer from 2 to 18.) 【Chemistry 3】 【Chemistry 4】

2. The composite of claim 1, which does not contain any other polymers other than the polyamide compound as a polymer.

3. 3. The composite according to claim 1, wherein the molar ratio of the dicarboxylic acid unit represented by the general formula (1):the dicarboxylic acid unit represented by the general formula (2) is 95:5 to 5:

95.

4. The composite according to claim 1 , wherein the talc content is 1% by mass or more and 40% by mass or less.

5. A method for producing the composite according to any one of claims 1 to 4, comprising the steps of: The polyamide compound and the talc are kneaded in a twin-screw kneading extruder.

Citation Information

Patent Citations

  • Polyamide resin composition

    JP1992091163A

  • Covering part made of resin for fuel feed system

    JP2007314673A

  • Reinforced thermoplastic resin composition

    JP2012036246A

  • Polyamide compound

    JP2018030913A

  • Polyamide compound, and method for producing polyamide compound

    JP2019137788A